Neuronal Degeneration: Its Neuropathological and Histopathological Aspects as One of the Causes of the Etiology of Alzheimers Disease (Global Journal of Medical Research, 2022)
Abstarct-This article aims to propose neuronal degeneration, and its neuropathological and histopathological aspects, as one of the causes of the etiology of Alzheimer's disease. The research had a qualitative approach and a bibliographic review, based on information from the last 10 years in the Scientific Electronic Library Online (Scielo), Digital Library of Theses and Dissertations (BDTD) and Digital Repository of the University of Beira (Ubibliorum) databases., website in general and consultations by reference theorists. The research concluded that there is a relationship between neuronal degeneration as one of the causes of AD etiology, and its histopathological and neuropathological aspects, such as accumulation of senile plaques composed of Ab-amyloid proteins, phospharization of tau protein, and neurotoxic gases from acetylcholimestarse enzyme.
Keywords: alzheimer's disease tau protein senile plaques acetylcholine